(untitled) (Dissertare, 2022)
The purpose of this research is to review the training and educational experiences of the students of the Health Statistics career at the Universidad de Los Andes, Venezuela, through the elaboration of a reading autobiography, in which experiences, practices, as well as positive and negative aspects derived from their learning of reading and writing, required in educational levels prior to university. Due to the conditions of social confinement, the virtual ethnography method was used with discussion groups and synchronous and asynchronous forums. At the end of the course, the autobiographies became a written production organized by each participant, from which fragments were intentionally selected. From the findings derived through the use of the discourse analysis technique, it was concluded that: the use of autobiography allows approaching the difficulties of the students, and their strengths and possible obstacles, on which the teacher must work. The family plays a fundamental role in the learning process, but the primary socialization factor is the one that creates a positive psychological climate for the appropriation of knowledge, the development of competencies and cognitive skills necessary to effectively overcome the demands of university culture. In short, the preparation of autobiographies at the beginning of each course is suggested, with the purpose of exploring weaknesses and aspects that require academic support.